2012
DOI: 10.1371/journal.pone.0038732
|View full text |Cite
|
Sign up to set email alerts
|

The Bimodal Lifestyle of Intracellular Salmonella in Epithelial Cells: Replication in the Cytosol Obscures Defects in Vacuolar Replication

Abstract: Salmonella enterica serovar Typhimurium invades and proliferates within epithelial cells. Intracellular bacteria replicate within a membrane bound vacuole known as the Salmonella containing vacuole. However, this bacterium can also replicate efficiently in the cytosol of epithelial cells and net intracellular growth is a product of both vacuolar and cytosolic replication. Here we have used semi-quantitative single-cell analyses to investigate the contribution of each of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
171
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(197 citation statements)
references
References 36 publications
17
171
0
Order By: Relevance
“…This is consistent with the low replication rate observed in vivo in acute or chronic infections and suggests the existence of mechanisms that restrict replication, but not survival, of bacteria inside the SCV [40]. Interestingly, replication in epithelial cells can also occur in the cytosol, and although it occurs only in less than 20% of infected cells, it accounts for the majority of the net replication [61]. In addition, in epithelial cells, a subset of SCVs is not maintained at a juxtanuclear position but moves towards the cell host periphery [62].…”
Section: Biogenesis Of the Salmonella-containingsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with the low replication rate observed in vivo in acute or chronic infections and suggests the existence of mechanisms that restrict replication, but not survival, of bacteria inside the SCV [40]. Interestingly, replication in epithelial cells can also occur in the cytosol, and although it occurs only in less than 20% of infected cells, it accounts for the majority of the net replication [61]. In addition, in epithelial cells, a subset of SCVs is not maintained at a juxtanuclear position but moves towards the cell host periphery [62].…”
Section: Biogenesis Of the Salmonella-containingsupporting
confidence: 80%
“…However, the behavior of a strain of S. enterica is different depending on the host cell type, and, although the SCV is a replicative niche in cultured epithelial cells and macrophages, this is not the case in fibroblasts or dendritic cells [40]. In addition, Salmonella can have a bimodal lifestyle in epithelial cells and replicate in the SCV and in the cytosol, as has been beautifully analyzed recently in human HeLa cells [61]. This issue is still more complex if we take into account the heterogeneity that is observed in tissue culture infection models, where neither all cultured host cells are infected nor all pathogen cells inflict alterations in host physiology [158].…”
Section: Different Lifestylesmentioning
confidence: 99%
“…We have previously used a spinning-disc confocal imaging system to image Salmonella-infected HeLa cells for up to 20 h p.i. (48). Here, we have used the same approach with M0 cells infected with Salmonella constitutively expressing the red fluorescent protein mCherry.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a sifA mutant of Salmonella fails to maintain vacuolar stability, and enters the cytosol of host cells within hours after infection, which results in activation of innate immune pathways and autophagy recruitment 8 . Vacuolar escape of Salmonella varies depending on the cell type that is studies, and several reports have shown that in epithelial cells even WT Salmonella can escape the SCV and hyperreplicate in the cytosol 10 . Recent reports show that innate immune detection of vacuolar pathogens also depends on the ability of the host to recognize and destabilize pathogen-containing vacuoles (PCVs) [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%